Testcross performance and combining ability of intermediate maturing drought tolerant maize inbred lines in Sub-Saharan Africa - Manigben, Kulai Amadu; Beyene, Yoseph; Chaikam, Vijay; Tongoona, Pangirayi B.; Danquah, Eric Y.; Ifie, Beatrice E.; Aleri, Isaiah; Chavangi, Andrew; Prasanna, Boddupalli M.; Gowda, Manje (Frontiers in Plant Science, 2024)
Drought is a major constraint on maize (Zea mays L.) production and productivity in Sub-Sahara Africa (SSA). The increase in frequency and severity of drought, driven by climate change, is expected to worsen in the future. These occurrences are likely to adversely affect maize production and productivity, threatening the economic and social stability of millions of smallholder farmers. Understanding the genetics of hybrids performance under drought stress is crucial for designing breeding strategies to develop high yielding hybrids. This study aimed to (i) evaluate the performance of three-way cross hybrids developed from elite inbred lines, including several drought tolerant lines, using a line-by-tester mating design, and (ii) estimate the general (GCA) and specific (SCA) combining ability effects of the tropical maize inbred lines under managed drought and optimal conditions. Two-hundred and sixty-five maize inbred lines from the CIMMYT global maize breeding program were used as parents and crossed to six single cross testers to generate 795 testcross hybrids. These hybrids, along with six commercial hybrids as a check, were evaluated under managed drought and optimum conditions. Significant (P<0.001) variations were observed among genotypes and genotypes by environment interactions (GEI) for grain yield and other traits. There was preponderance of GCA variance (lines and tester) over SCA variance, indicating that additive effects were more important in determining grain yield and other traits under both managed drought and optimal conditions. Ten inbred lines with desirable GCA effects for grain yield and other traits were identified. Fourteen testcross hybrids were identified with high grain yield and desirable agronomic traits under both drought and optimal conditions. The identified lines and hybrids are useful sources to be used in breeding and deploying as a stress-tolerant hybrids. High correlations observed between observed and GCA predicted hybrid performance suggests the possibility to evaluate more hybrids with fixed resources. The study demonstrates that it is feasible to obtain high yielding and drought tolerant lines and hybrids. These testcross hybrids should undergo rigorous on-farm trials to ensure consistent performance before commercialization and release. Deploying these hybrids could help in mitigating the effects of drought stress in SSA.